The Application of Carrying Capacity Concept for Sustainable Development in Small Island (Case Study Kaledupa Islands, Distict Wakatobi) - Muh. Rasman Manafi; Achmad Fahrudin; Dietriech G. Bengen; Mennofatria Boer (Institut Pertanian Bogor, 2009)
The Challenge for small islands planners and managers in Indonesia right now is to develop resources and environment service of small islands for the maximum benefit and, at the same time, to maintain the sustainable capacity of ecosystems (meaning does not exceed the carrying capacity of the ecosystems). This paper applied carrying capacity concept for sustainable development of small islands. To determine carrying capacity of utility space of small islands through two aspects: (1) freshwater, and (2) spaces. Analysis result of carrying capacity for directing utility land area (settlements and agricultures), the freshwater aspects would be fullness, if annual absorption to rainy stayed at 50%. The space area of aquatic which could be utilized for marine culture, shore and marine ecotourism there were around 70%. It was 30% recommended for marine protected zone.Keywords: sustainable development, small islands, carrying capacity .